Insights on the functional interactions between miRNAs and copy number variations in the aging brain - Persengiev, Stephan; Kondova, Ivanela; Bontrop, Ronald (Frontiers in Molecular Neuroscience, 2013)
MicroRNAs (miRNAs) are regulatory genetic elements that coordinate the expression of thousands of genes and play important roles in brain aging and neurodegeneration. DNA polymorphisms affecting miRNA biogenesis, dosage and gene targeting may represent potentially functional variants. The consequences of single nucleotide polymorphisms (SNPs) affecting miRNA function were previously demonstrated by both experimental and computational methods. However, little is known about how copy number variations (CNVs) influence miRNA metabolism and regulatory networks. We discuss potential mechanisms of CNVs-mediated effects on miRNA function and regulation that might have consequences for brain aging. We argue that CNVs, which potentially can alter miRNA expression, regulation or target gene recognition, are possible functional variants and should be considered high priority candidates in genotype-phenotype mapping studies of brain-related disorders.